A comparative study of the lifelong learning propensities of English language learners: nationality, gender and length of study. Issue 1 (1st June 2015) - Deveci, Tanju
Abstract : Acquiring a foreign language may be a lifelong endeavor, and this requires one to approach it from a lifelong learning perspective. However, learners may not always be ready for such an approach. It is important to know where learners stand in their orientations toward learning and consider this when planning educational activities. Therefore, it is necessary to determine language learners' readiness for lifelong learning (LLL) in order to support their language development. This paper reports the findings of a study conducted to identify the LLL propensities of some Turkish and Emirati university students learning English as a foreign language in their local contexts. The study included 61 Emirati and 47 Turkish students, with a mean age of 19. Data were collected using a research tool with three sections: Demographics, the Lifelong Learning Tendency Scale (LLLTS – developed by Coskun & Demirel (2012)), and a survey with six open-ended questions. Student's t-test, the Kruskal-Wallis test and the Mann-Whitney U-test were used to compare the quantitative data in terms of the participants' nationalities, gender and length of study. The results showed that both Turkish and Emirati students had a moderate level of propensity for LLL. However, the Turkish students' overall LLLTS scores as well as certain sub-skills were found to be higher than those of the Emirati students. Gender was not found to make a significant difference in the students' LLL orientations, while motivation was found to be lower at a statistically significant level for those learning English for more than a year. Suggestions are offered for the development of language learners' LLL skills.